Analisis Sistem Pengendalian Intern dalam Menunjang Efektivitas Prosedur Pemberian Kredit pada KSP Kopdit Hiro Heling Cabang Utama - Silviana, Maria; Dince, Maria Nona; Rengga, Andreas (BUDGETING : Journal of Business, Management and Accounting, 2024)
This reaseach aims to determine the implementation of internal control system in supporting the effectiveness of the credit granting system at KSP Kopdit Hiro Helingmain branch.Data collection used in this research used interview and observation methods.This type of research used qualitative descriptive analysis techniques by comparing the internal control system thas been implemented at KSP Kopdit Hiro Heling with the internal control system according to COSO Framework (2011).The results of this research indicate that the implementation of an internal control system to support the effectiveness of kredit granting procedures at KSP Kopdit Hiro Heling main branch and according to the COSO Framework (2011) has beeb implemented but there is still an internal control component,namely the control environment in inadequate because the organizational structure does not yet special staff at SPI (internal supervisory unit) Keywords : Credit Granting Procedure, Intenal control system.